2022
DOI: 10.2460/ajvr.21.02.0024
|View full text |Cite
|
Sign up to set email alerts
|

Fecal extract from obese horses induces an inflammatory response by murine macrophages in vitro

Abstract: OBJECTIVE To compare the inflammatory response of murine macrophages exposed to the enteric microbiome of obese horses versus nonobese horses. SAMPLE Fecal samples from 12 obese horses (body condition score ≥ 7/9) and 12 nonobese horses (body condition score 4 to 5/9) with similar dietary management. PROCEDURES Fecal supernatant was prepared from frozen fecal samples. RAW 264.7 macrophage cells were exposed to the fecal extract. Inflammatory cytokine (interleukin-1β, tumor necrosis factor-α, and interleuki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…In a diet-controlled study with a more homogenous population, fecal microbiome diversity and Bacteroidetes abundance were increased in obese horses [70]. In addition, murine macrophages exposed to fecal extracts from obese horses exhibited increased expressions of inflammatory markers such as IL-1β, TNF-α, and IL-6 when compared to those exposed to fecal extracts from non-obese horses [71].…”
Section: Diet and Obesitymentioning
confidence: 93%
“…In a diet-controlled study with a more homogenous population, fecal microbiome diversity and Bacteroidetes abundance were increased in obese horses [70]. In addition, murine macrophages exposed to fecal extracts from obese horses exhibited increased expressions of inflammatory markers such as IL-1β, TNF-α, and IL-6 when compared to those exposed to fecal extracts from non-obese horses [71].…”
Section: Diet and Obesitymentioning
confidence: 93%
“…Horses with metabolic syndrome have been shown to harbor distinct intestinal microbiota and metabolites compared to healthy controls [ 92 , 103 ]. Furthermore, an in vitro study showed that macrophage cells exposed to fecal extracts obtained from obese horses induced a higher production of proinflammatory cytokines compared to extracts from non-obese horses, suggesting a potential role of the microbiota composition in obese horses [ 104 ]. The diseases associated with altered intestinal microbiota have been reviewed elsewhere [ 13 , 32 ].…”
Section: Factors Influencing Microbiota Compositionmentioning
confidence: 99%
“…Obesity in horses has been associated with metabolic alterations and diseases, including insulin resistance [ 22 ], alterations of adipose tissue and cardiovascular function [ 23 , 24 ], low-grade inflammation [ 25 ] and weakened immunity [ 26 ], equine metabolic syndrome [ 27 ], and laminitis [ 28 ], as well as changes in the composition [ 29 ] and function [ 30 ] of the gut microbiota. Obesity can also negatively impact sports performances [ 31 ], as well as the physiological response to exercise and locomotion symmetry [ 32 ].…”
Section: Introductionmentioning
confidence: 99%